2019
DOI: 10.3389/fneur.2019.00278
|View full text |Cite
|
Sign up to set email alerts
|

Time of Day and a Ketogenic Diet Influence Susceptibility to SUDEP in Scn1aR1407X/+ Mice

Abstract: Sudden unexpected death in epilepsy (SUDEP) is a major cause of mortality in patients with drug-resistant epilepsy. Most SUDEP cases occur in bed at night and are preceded by a generalized tonic-clonic seizure (GTCS). Dravet syndrome (DS) is a severe childhood-onset epilepsy commonly caused by mutations in the SCN1A gene. Affected individuals suffer from refractory seizures and an increased risk of SUDEP. Here, we demonstrate that mice with the Scn1a R1407X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 41 publications
9
34
0
Order By: Relevance
“…Previous studies demonstrated that increased seizure burden during the worsening stage correlates with increased risk for SUDEP Teran et al, 2019). Here, we add that reduced PSD also correlates with increased risk for SUDEP ( Fig.…”
Section: Reduced Eeg Power At the Worsening Stage Of Dravetsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies demonstrated that increased seizure burden during the worsening stage correlates with increased risk for SUDEP Teran et al, 2019). Here, we add that reduced PSD also correlates with increased risk for SUDEP ( Fig.…”
Section: Reduced Eeg Power At the Worsening Stage Of Dravetsupporting
confidence: 69%
“…1A), such longitudinal analysis inherently disregards these mice that die prematurely. Moreover, as frequent seizures have been shown to increase the risk of sudden unexpected death in epilepsy (SUDEP) Teran et al, 2019), this analysis also intrinsically selects mice with milder epilepsy or better compensatory mechanisms, which enable survival to the stabilization stage. A comparison of the PSD between mice that died prematurely and those that survived to the stabilization stage demonstrated decreased power in mice which eventually died during the worsening stage ( Fig.…”
Section: The Risk For Premature Death Correlates With Lower Psdmentioning
confidence: 99%
“…Previous studies demonstrated that the occurrence of premature death during the severe stage of the epilepsy correlates with higher seizure burden. 22,25 Within this cohort of DS mice, 56% of the mice died during the 4th week of life. Thus, we wondered whether worse performance at the pre-epileptic stage would correlate with a higher risk for premature death.…”
Section: Dravetmentioning
confidence: 99%
“…79,80 The ketogenic diet, an alternative seizure treatment for refractory epilepsy, reduces the mortality in SCN1A R1407X/þ mice without modifying seizure frequency or light-dark predilection. 35 Moreover, the ketogenic diet reduces seizure number and extends longevity in KCNA1-null mice, in a gender-and age-dependent manner. [41][42][43] In addition, rest deficiency seen in KCNA1-null mice is reduced with ketogenic diet treatment.…”
Section: Arousal Sleep and Time Of Daymentioning
confidence: 99%